Peningkatan Kinerja UKM Bambu Klaten Melalui Pengembangan Desain dan Manajemen Keuangan - Dewi Kusuma Wardani; Novita Wahyuningsih; JONET ARIYANTO NUGROHO; Muhammad Sabandi (LPPM UNS, 2014)
Science and technology activities for the community was held in bamboo handicraft business partners belonging to Wahyu Purnomo and Supri. Both Small and Medium Enterprises (SME5) partners produce home furniture and souvenirs using bamboo as the main material. The activities was located in Jambu Kulon village in district of Ceper, which is 13km from the city of Klaten or 33 km from the city of Surakarta. Issues to be solved in this activity are: bamboo craft designs that are not varied and bamboo SMEs have not implemented financial statements in conformity minimum accounting standards.Problems solving through the development of design (shape and color combination) and applying accounting training in accordance with the minimum accounting standards that are tailored to the needs and capabilities of SMEs bamboo. Using training and supervision individually or in groups, the results shows that: 1 ) Design a corner chair and chaise lounge on the Bamboo SMEs belongs to Supri has done. 2) Batik mega mendung design in a duck's handicraft and innovation of the form of a duck as a pencil case has implemented. 3) The financial statements conform to accounting standards minimum for bamboo SME has trained, which includes daily cash flow, purchases journal, sales journal, and income statement.